Exploring the Theoretical Gap on Knowledge Work of Knowledge and Skilled Workers in TVET Practices: A Literature Review - Janis, Ilyana; Paimin , Aini Nazura; Alias, Maizam (Journal of Technical Education and Training, 2021)
This article presents a literature review on the theoretical gap of knowledge work between knowledge and skilled workers. There are two primary reasons for conducting this literature review namely the lack of literature on knowledge work for skilled workers and, the poor understanding of their knowledge requirements. Although the requirements for the Industry 4.0 skilled-workers, knowledge work, and innovation are widely discussed in the literature for white-collar jobs, there are scarcely mentioned for blue-collar jobs. Also, the theoretical gap of knowledge between skilled workers and knowledge workers has not been yet addressed, leading to poor public perception of the role of knowledge work in TVET skilled workers. The findings from this literature review may provide insights into the understanding of the theoretical gap and the role of knowledge work for skilled workers and knowledge workers. Seventy-seven articles were reviewed, and inductive thematic analysis was conducted with ATLAS.ti resulting in three major themes, namely, ‘qualification and employment requirement’, ‘management control’, and ‘theoretical and contextual perspectives. The findings indicate that there are differences in knowledge work identified in two groups of workers, nonetheless, support the conclusion that knowledge works are equally crucial for skilled workers to optimise their role. The findings of this study imply that the role of the two groups of workers could not be described interchangeably within a similar working-class and these findings could be used to create clear distinction in the definition and descriptions of work practices of knowledge and skilled workers within the TVET sectors.